Analisis Faktor-Faktor Penggunaan Quizizz Untuk Menunjang Kemampuan Numerasi Siswa SMP Kota Bengkulu - Desventri Etmy; Agus Susanta; Nurul Astuty Yensy (FKIP Universitas Mataram, 2025)
Indonesia’s low numeracy performance in international assessments highlights the need for more effective and engaging instructional strategies. This study analyzed the influence of the Quizizz application on supporting the numeracy ability of junior high school students in Bengkulu City. Using a quantitative approach, data were collected from 70 students through a Likert-scale questionnaire measuring ten indicators of Quizizz utilization. Multiple linear regression analysis using SPSS 25 revealed that the model was statistically significant (F = 3.303; p = 0.002), with the independent variables collectively explaining 36.3% of the variance in numeracy skills (Adjusted R² = 0.253). Two indicators—conceptual understanding (x1) and critical–creative thinking (x5)—significantly affected numeracy ability, whereas other indicators showed no partial influence. The model met classical assumption requirements, including linearity and homoscedasticity. These findings confirm that Quizizz is an effective digital learning tool that enhances students’ numeracy through interactive and motivating learning experiences.